Atmospheric and Fluvial Nutrients Fuel Algal Blooms in the East China Sea - Mackey, Katherine R. M.; Kavanaugh, Maria T.; Wang, Fujiang; Chen, Ying; Liu, Fei; Glover, David M.; Chien, Chia-Te; Paytan, Adina (Frontiers in Marine Science, 2017)
Chinese coastal waters support vast fisheries and vital economies, but their productivity is threatened by increasingly frequent harmful algal blooms (HABs). Here we provide direct experimental evidence that atmospheric deposition, along with riverine input, opens new niches for bloom-forming dinoflagellates and diatoms in the East China Sea (ECS) by increasing the ratio of nitrogen to phosphorus (N:P), inducing severe P limitation, and altering trace metal micronutrient inventories. Remote sensing analysis of blooms in the region showed that dinoflagellate blooms were associated with increased aerosol optical thickness and decreased sea surface temperature, whereas diatom blooms were primarily associated with seasonally decreased temperature (e.g. during spring blooms). Bottle incubation experiments revealed that aerosol additions approximating 10 days of strong deposition increased iron availability and intensified P limitation, which together promoted dinoflagellate growth in offshore waters. Diatom growth was correlated with elevated trace metal and nutrient content from aerosols. Aerosols did not induce phytoplankton growth at a station within the Yangtze River plume where light was limiting, consistent with remote sensing observations that aerosol effects are stronger in offshore waters. Eutrophication and trace metal enrichment from Yangtze River discharge together with atmospheric deposition may underlie the transition from diatom-dominated spring blooms toward more frequent spring and summer dinoflagellate blooms that has occurred over the past three decades in the ECS.